Civil Religion dan Masa Depan Umat Beragama di Indonesia: Mempertemukan Ideologi Keagamaan dan Ideologi Kebangsaan - Irham, Muhammad Aqil (AL-ADYAN, 2017)
The rise of religious ideological movements and national ideology in Indonesia is still felt today. As a result of that, there are often truth claims that sometimes end in chaos in the public. So to mediate it all requires an independent and neutral view. The view referred to is none other than the existence of a civil religion. Civil religion or "religious attitude that is owned by citizens". Civil religion is not at all to shift the position of religion that exists and is believed by society in a country. This study includes the type of library research (library research) which will rely on the source of data obtained from library materials both books, articles, journals, newspapers and other literature that supports and fits with the major themes of this research; among others concerning civil religion, religious ideology, national ideology, and the future of religious people in Indonesia. The nature of this research is descriptive-qualitative, namely trying to explain various problems and findings carefully and in detail by connecting various data, so that a clear, accurate and factual picture is obtained in accordance with the focus of the research. The right way out to bring together religious ideology and national ideology is by applying civil religion; where in practice civil religion is respecting differences, strengthening equality, tolerance, freedom from acts of intimidation, assault and so on.